2012
DOI: 10.1007/s00404-012-2470-8
|View full text |Cite
|
Sign up to set email alerts
|

Delivery mode and the course of pre- and postpartum depression

Abstract: DM only showed coherence with the extent of depression briefly during the peripartal period. A relationship was found between depressiveness during pregnancy and DM, with higher depressiveness scores in the group of patients undergoing primary CS. This should be taken into account when patients requesting an elective cesarean section are being counseled.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 44 publications
2
26
1
3
Order By: Relevance
“…This inconsistency may reflect differences in study design, including the modes of delivery examined, the assessment instruments used, and the adjustments of covariates. In addition, we found no differences in the prevalence of depressive symptoms between the two groups at 4-6 weeks or at 6 and 12 months postpartum, consistent with the data of previous cross-sectional studies (Josefsson et al, 2002;Rauh et al, 2012;Sword et al, 2011) and follow-up studies conducted at 2 and 4 months postpartum (Sadat et al, 2014) and at 4 and 12 months postpartum (Durik et al, 2000). The cesarean group had a higher frequency of depressive symptoms at 3 months postpartum than did the vaginal group.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This inconsistency may reflect differences in study design, including the modes of delivery examined, the assessment instruments used, and the adjustments of covariates. In addition, we found no differences in the prevalence of depressive symptoms between the two groups at 4-6 weeks or at 6 and 12 months postpartum, consistent with the data of previous cross-sectional studies (Josefsson et al, 2002;Rauh et al, 2012;Sword et al, 2011) and follow-up studies conducted at 2 and 4 months postpartum (Sadat et al, 2014) and at 4 and 12 months postpartum (Durik et al, 2000). The cesarean group had a higher frequency of depressive symptoms at 3 months postpartum than did the vaginal group.…”
Section: Discussionsupporting
confidence: 93%
“…After adjustment for covariates, we found no association between depressive symptoms and delivery mode in the Table 2 Differences in depressive symptoms and pain between vaginal delivery (n = 200) and cesarean delivery ( early postpartum period (e.g., 3-5 days), which is not consistent with the findings of previous studies that reported a higher rate of depressive symptoms after cesarean than after spontaneous delivery at 2-3 days postpartum (Rauh et al, 2012) and a significant association between cesarean delivery and depressive symptoms at 5 days postpartum (Bergant et al, 1998). This inconsistency may reflect differences in study design, including the modes of delivery examined, the assessment instruments used, and the adjustments of covariates.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…6 Additional risk factors include lack of social support, stressful life events, and pregnancy complications. 4,6,7 Numerous studies have explored the association between cesarean delivery and postpartum depression, [8][9][10][11][12][13][14][15][16] and most studies have concluded that mode of delivery is not a predictor. [8][9][10][11]13,15 However, a patient's antepartum delivery preferences may play an important role in the determination of how a woman perceives her childbirth experience and outcome, which potentially could affect her risk for postpartum depression.…”
mentioning
confidence: 99%
“…Helplessness and loss of control during birth were both associated with higher depression rates in the postpartum period [4]. Furthermore, delivery mode and genetic polymorphisms could be identified as potential risk factors for the development of peripartal depression [5][6][7]. Therefore, these factors can be useful for identifying women who should be offered an intervention to prevent possible negative effects on the mother or child.…”
mentioning
confidence: 99%